2022
DOI: 10.1038/s41598-022-26392-8
|View full text |Cite
|
Sign up to set email alerts
|

Power spectrum and critical exponents in the 2D stochastic Wilson–Cowan model

Abstract: The power spectrum of brain activity is composed by peaks at characteristic frequencies superimposed to a background that decays as a power law of the frequency, $$f^{-\beta }$$ f - β , with an exponent $$\beta $$ β close to 1 (pink noise). This exponent is predicted to be connected with the exponent $$\gamma $$ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Alternatively, a recent work has shown that, in a 2D Wilson-Cowan neural network, the value of the exponent k is related to the network connectivity, with for a 2D connectivity, and when the mean-field approximation holds. 77 This may suggest that, in our case, the mean-field approximation is justified for relatively small avalanches involving few electrodes, but not for large-scale EEG avalanches. However, to verify whether this is due to the structure of the underlying, collective neural activity, simultaneous multi-scale recordings would be needed.…”
Section: Discussionmentioning
confidence: 71%
“…Alternatively, a recent work has shown that, in a 2D Wilson-Cowan neural network, the value of the exponent k is related to the network connectivity, with for a 2D connectivity, and when the mean-field approximation holds. 77 This may suggest that, in our case, the mean-field approximation is justified for relatively small avalanches involving few electrodes, but not for large-scale EEG avalanches. However, to verify whether this is due to the structure of the underlying, collective neural activity, simultaneous multi-scale recordings would be needed.…”
Section: Discussionmentioning
confidence: 71%
“…We cannot rule out that the exponent of the PSD captures other signal properties beyond E/I balance (e.g. criticality 109 ). The largest part of the literature investigating the PSD features in epilepsy has seldom disentangled the periodic from the aperiodic component.…”
Section: Limitationsmentioning
confidence: 97%
“…It has been proposed that the brain experiences both continuous phase transitions with scale-free avalanches, and discontinuous transitions, which are beneficial for self-sustained replay activity and memory functioning [20][21][22]. The roles of topology and learning have also been investigated [11,[23][24][25][26][27], with some notable insights on the role of modularity [28,29].…”
Section: Introductionmentioning
confidence: 99%